KEBANGKITAN AGAMA DAN PRASANGKA SEKULER DALAM KAJIAN HUBUNGAN INTERNASIONAL - Akhmad Jatmiko (Program Magister Ilmu Politik, Universitas Diponegoro, 2017)
AbstractThe global resurgence of religion seems nowadays to generate repression as it tends to create international instability, political upheaval and chaotic states. Most political scientist and intelligence experts did not predict the resurgence because it was not supposed to happen in a country participating so thoroughly in modernization and Westernization. It is interesting to learn that so many scholars and policymakers who monitored the international politics have missed the warning signs about the resurgence. It because of the argument that religion was the object that needed to vanish for modern international politics to come into being. Religion has been, and largely remains, what the discipline of International Relations (IR) can speak about only as a threat to its own existence. This paper tries to explain how the resurgence of religion has been on the spotlight in the eyes of IR Study. It also explains that the IR Study now faces a serious dilemma to treat religion in such a proper way. Various arguments on the strategy to deal with religion has come up that makes religion a more and more interesting subject in academic realms.Kata Kunci: Kebangkitan agama, modernisasi, pencerahan, sekularisasi, Westphalia